Transessualismo : guida alla decisione, come affrontare la disforia di genere. - Lambillotte, Deborah; Ceccarelli, Franca; Bertoldi, Isabel (Milano : Arcitrans nazionale, 2001)
Fonds Suzan Daniel (FSD)
Italiaans
Brochure